Genetic and non-genetic factors affecting the expression of COVID-19-relevant genes in the large airway epithelium. - Kasela, Silva; Ortega, Victor E; Martorella, Molly; Garudadri, Suresh; Nguyen, Jenna; Ampleford, Elizabeth; Pasanen, Anu; Nerella, Srilaxmi; Buschur, Kristina L; Barjaktarevic, Igor Z; Barr, R Graham; Bleecker, Eugene R; et al. (Genome Med, 2021)
BACKGROUND: The large airway epithelial barrier provides one of the first lines of defense against respiratory viruses, including SARS-CoV-2 that causes COVID-19. Substantial inter-individual variability in individual disease courses is hypothesized to be partially mediated by the differential regulation of the genes that interact with the SARS-CoV-2 virus or are involved in the subsequent host response. Here, we comprehensively investigated non-genetic and genetic factors influencing COVID-19-relevant bronchial epithelial gene expression. METHODS: We analyzed RNA-sequencing data from bronchial epithelial brushings obtained from uninfected individuals. We related ACE2 gene expression to host and environmental factors in the SPIROMICS cohort of smokers with and without chronic obstructive pulmonary disease (COPD) and replicated these associations in two asthma cohorts, SARP and MAST. To identify airway biology beyond ACE2 binding that may contribute to increased susceptibility, we used gene set enrichment analyses to determine if gene expression changes indicative of a suppressed airway immune response observed early in SARS-CoV-2 infection are also observed in association with host factors. To identify host genetic variants affecting COVID-19 susceptibility in SPIROMICS, we performed expression quantitative trait (eQTL) mapping and investigated the phenotypic associations of the eQTL variants. RESULTS: We found that ACE2 expression was higher in relation to active smoking, obesity, and hypertension that are known risk factors of COVID-19 severity, while an association with interferon-related inflammation was driven by the truncated, non-binding ACE2 isoform. We discovered that expression patterns of a suppressed airway immune response to early SARS-CoV-2 infection, compared to other viruses, are similar to patterns associated with obesity, hypertension, and cardiovascular disease, which may thus contribute to a COVID-19-susceptible airway environment. eQTL mapping identified regulatory variants for genes implicated in COVID-19, some of which had pheWAS evidence for their potential role in respiratory infections. CONCLUSIONS: These data provide evidence that clinically relevant variation in the expression of COVID-19-related genes is associated with host factors, environmental exposures, and likely host genetic variation.
Keywords: Adult; Aged; Aged, 80 and over; Angiotensin-Converting Enzyme 2; Asthma; Bronchi; Cardiovascular Diseases; COVID-19; Gene Expression; Genetic Variation; Humans; Middle Aged; Obesity; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; Respiratory Mucosa; Risk Factors; SARS-CoV-2; Smoking

Mutation of CFAP57, a protein required for the asymmetric targeting of a subset of inner dynein arms in Chlamydomonas, causes primary ciliary dyskinesia. - Bustamante-Marin, Ximena M; Horani, Amjad; Stoyanova, Mihaela; Charng, Wu-Lin; Bottier, Mathieu; Sears, Patrick R; Yin, Wei-Ning; Daniels, Leigh Anne; Bowen, Hailey; Conrad, Donald F; Knowles, Michael R; Ostrowski, Lawrence E; et al. (PLoS Genet, 2020)
Primary ciliary dyskinesia (PCD) is characterized by chronic airway disease, reduced fertility, and randomization of the left/right body axis. It is caused by defects of motile cilia and sperm flagella. We screened a cohort of affected individuals that lack an obvious axonemal defect for pathogenic variants using whole exome capture, next generation sequencing, and bioinformatic analysis assuming an autosomal recessive trait. We identified one subject with an apparently homozygous nonsense variant [(c.1762C>T), p.(Arg588*)] in the uncharacterized CFAP57 gene. Interestingly, the variant results in the skipping of exon 11 (58 amino acids), which may be due to disruption of an exonic splicing enhancer. In normal human nasal epithelial cells, CFAP57 localizes throughout the ciliary axoneme. Nasal cells from the PCD patient express a shorter, mutant version of CFAP57 and the protein is not incorporated into the axoneme. The missing 58 amino acids include portions of WD repeats that may be important for loading onto the intraflagellar transport (IFT) complexes for transport or docking onto the axoneme. A reduced beat frequency and an alteration in ciliary waveform was observed. Knockdown of CFAP57 in human tracheobronchial epithelial cells (hTECs) recapitulates these findings. Phylogenetic analysis showed that CFAP57 is highly conserved in organisms that assemble motile cilia. CFAP57 is allelic with the BOP2/IDA8/FAP57 gene identified previously in Chlamydomonas reinhardtii. Two independent, insertional fap57 Chlamydomonas mutant strains show reduced swimming velocity and altered waveforms. Tandem mass tag (TMT) mass spectroscopy shows that FAP57 is missing, and the "g" inner dyneins (DHC7 and DHC3) and the "d" inner dynein (DHC2) are reduced, but the FAP57 paralog FBB7 is increased. Together, our data identify a homozygous variant in CFAP57 that causes PCD that is likely due to a defect in the inner dynein arm assembly process.
Keywords: 3T3 Cells; Adult; Animals; Axoneme; Cells, Cultured; Chlamydomonas reinhardtii; Cilia; Ciliary Motility Disorders; Codon, Nonsense; Conserved Sequence; Dyneins; Humans; Male; Mice; Microtubule-Associated Proteins; Plant Proteins; Proteins; Respiratory Mucosa